USE OF FOREIGN EXPERIENCES IN ENSURING EFFECTIVENESS OF GEOGRAPHY EDUCATION (Conference Zone, 2022)
In this article, the experience of foreign countries in the development of geographical education is thoroughly studied. In particular, the experience of the USA, Germany, Finland, and South Korea has been studied and ways of their popularization in the conditions of Uzbekistan have been shown.